Leadership Communication Styles and Supply Chain Performance Among Selected Managers of Aviation Manufacturing Company: Basis for Action Plan - Marino, Celica L. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined the relationship between leadership communication styles and supply chain performance among selected managers in an aviation manufacturing company located in Tanauan City, Batangas. Grounded in Transformational Leadership Theory, Leader-Member Exchange (LMX) Theory, and the SCOR Model Framework, the study aimed to assess the influence of directive, participative, transformational, and laissez-faire communication on efficiency, on-time delivery, and inventory management. A descriptive-correlational design was employed using a structured questionnaire distributed to 63 randomly selected managers from planning, procurement, logistics, and inventory departments. Findings revealed that participative, directive, and transformational communication styles were predominantly used, all rated “Very High,” while laissez-faire communication was least used though still rated at a high level. Managers demonstrated excellent supply chain performance across all indicators, with mean scores suggesting they consistently exceeded expectations in efficiency (M=3.43), on-time delivery (M=3.42), and inventory management (M=3.28). Spearman Rho and Kendall’s Tau-B tests revealed moderate, statistically significant relationships between leadership communication styles and supply chain performance (p=0.001). However, the Kruskal-Wallis H test indicated no significant difference in performance across communication styles (p=0.189), suggesting that contextual application of styles may be more critical than style alone. An action plan was proposed to enhance leadership communication through training, technological tools, and cross-functional alignment. The findings highlight the strategic value of adaptive communication styles in strengthening supply chain effectiveness in aviation manufacturing.